Molecular Level Characterization of Diatom and Coccolithophore-Associated Biopolymers That Are Binding 210Pb and 210Po in Seawater - Lin, Peng; Xu, Chen; Xing, Wei; Santschi, Peter H. (Frontiers in Marine Science, 2021)
Through a combination of selective extractions and molecular characterization techniques including Isoelectric Focusing Chromatography and Electrospray Ionization Fourier-Transform Ion Cyclotron Resonance Mass spectrometry, molecular structures of diatom (Phaeodactylum tricornutum) and coccolithophore (Emiliania huxleyi)-associated biopolymers that are responsible for the distinct partitioning behavior between 210Pb and 210Po were determined. Our results show that diatom-derived biopolymers have distinctive elemental grouping distributions as compared to those excreted by the coccolithophore, with the former consisting of more heterogeneous elements (i.e., nitrogen, sulfur and phosphorus-containing organic compounds). For the coccolithophore culture, two 210Pb-enriched biopolymers (non-attached exopolymeric substances and coccosphere shell-associated biopolymers) have a higher abundance of CHO-type compounds, suggesting CHO-only-type compounds as the main binding moieties for 210Pb. In contrast, such association was not evident in the diatom culture. Different with 210Pb, 210Po enrichment in coccolithophore-derived attached exopolymeric substances and Fe-Mn-associated metabolites coincided with the higher abundance of nitrogen/sulfur-containing organic compounds in these two biopolymer fractions, suggesting the strong parallel of Po with the production of nitrogen-rich organic matter as well as sulfur-containing amino acids. These different associations between 210Pb/210Po and organic functional groups were further explored by separating 210Pb or 210Po-labeled coccolithophore-derived biopolymers via isoelectric focusing. This technique suggests that phosphate group-containing molecules but not the other molecules that contain heterogeneous elements (e.g., CHONS, CHON, and CHOS) as the strongest binding agents for 210Pb, while the more hydrophobic (high protein to carbohydrate ratio) nitrogen/sulfur-enriched organic moieties acted as the main 210Po-binding ligands. It is concluded that the deficiency of 210Po with respect to 210Pb can be influenced by the relative abundance of nitrogen/sulfur-enriched organic moieties to the nitrogen/sulfur-depleted organic compounds in the water column. This behavior constrains the application of 210Po-210Pb approach to quantify the particulate organic carbon (POC) export flux in the ocean. It also explains that differences in chemical binding of the 210Po as compared to those of other radionuclides (e.g., thorium-234) as the main factor. That suggests that differences in decay half-lives or physical factors are less important when these nuclides are applied to estimate the POC flux in the ocean.